The Concept of Commiseration with the ’’Enemy’’ Within War Literature - Mariwan Hwayyiz Rustum (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The subject of war and literature has garnered a great deal of critical attention; nevertheless, this special issue concentrates on literary texts that examine the concept of commiseration with the "enemy" within war literature. Texts that depict authors and/or literary characters attempting to comprehend the motives, beliefs, cultural values, and of those who have been labelled as enemies by their nations often indicate that the soldier has begun a process of reflection about why he or she is a part of the war experience. These writings also demonstrate how political authorities frequently use propaganda and myth-making strategies to convince soldiers that they are fighting opponents that are terrible, subhuman, and hence are their direct foes. Literary works that demonstrate an author and/or literary character reflecting on state-supported definitions of good/evil, right/wrong, ally/enemy can provide a chance to reassess the aims of war, as well as one’s moral role during combat. With the fear of war, a constant reality in the modern period, it is crucial to recognize literary texts that reflect on the political manipulation of belief during warfare that drives one to accept intolerance against others by maintaining a designation that they are the enemy. This issue is particularly interested in receiving pieces that explore writings produced from the perspective of troops considering why they are fighting. Texts that center on a soldier’s meditation on what their opponent may be like, who they are, what they believe, and so on are popular are much desired.